SuPAR is associated with death and adverse cardiovascular outcomes in patients with suspected coronary artery disease. (1st November 2020) - Hodges, Gethin; Lyngbæk, Stig; Selmer, Christian; Ahlehoff, Ole; Theilade, Simone; Sehestedt, Thomas Berend; Abildgaard, Ulrik; Eugen-Olsen, Jesper; Galløe, Anders Michael; Hansen, Peter Riis; Jeppesen, Jørgen L.; Bang, Casper N.
Abstract: Background: The inflammatory biomarker soluble urokinase plasminogen activator receptor (suPAR) is associated with presence and severity of coronary artery disease (CAD) and incident death and myocardial infarction (MI). We sought to validate this finding in a further cohort of patients with suspected CAD. Methods: Plasma suPAR was available in 1635 patients (73% with CAD) undergoing coronary angiography at a single regional Danish hospital between 2003 and 2005. Patients were followed for adverse cardiovascular outcomes of death, cardiac death and MI over a median follow-up of 4.2 years. Results: In multivariate Cox models, adjusted for established cardiovascular risk factors, the biomarkers C-reactive protein, troponin-T and N-terminal-pro brain natriuretic peptide and the number of stenotic vessels, suPAR was independently associated with the combined endpoint of death/MI, hazard ratio (HR) 1.88; cardiovascular death, HR 2.01; and non-fatal MI, HR 1.53; (all p ≤ .037) per doubling of suPAR concentration. A plasma cutoff for suPAR ≥ 3.5 ng/mL was also significantly associated with death/MI, HR 1.51; p = .005. The C-statistic for the multivariate model predicting death/MI improved from 0.712 to 0.730 ( p for difference .008) after inclusion of suPAR. However, suPAR was not associated with presence or extent of CAD ( p > .05). Conclusion: These results validate previous findings that demonstrate suPAR to be an independent predictor of death/MI in patients with suspected or known CAD, however suPAR was not associated with presence or extent of CAD in our cohort. Probably because suPAR reflects end organ damage rather than the degree of atherosclerosis. BRIEF SUMMARY: We demonstrate that the inflammatory biomarker soluble urokinase plasminogen activator receptor is an independent predictor of death/myocardial infarction in patients with suspected or known coronary artery disease, but is not associated with the presence or severity of coronary artery disease.